The Effectiveness of Flashcard Media in Enhancing Indonesian Language Proficiency in Elementary Schools: A Systematic Literature Review - Putri, Berlianti Eka; Mahendra, Yasinta; Suprapto, Irawan; Junaidi (Journal for Lesson and Learning Studies, 2024)
The challenges of low student interest, limited resources, and a lack of engaging teaching media remain significant obstacles in teaching the Indonesian language in elementary schools. This study aims to analyze the effectiveness of using flashcard media to improve the Indonesian language proficiency of elementary school students. The method employed is a systematic literature review (SLR) with qualitative data analysis based on relevant studies. Data were collected from various related literature to identify key findings and research gaps. The results indicate that flashcard media has proven effective in enhancing Indonesian language learning outcomes. Key findings from the literature reveal that publications related to flashcard usage peaked in 2023, while the lowest number of publications occurred in 2019. Flashcard media allows students to learn in a more interactive and engaging manner, which can increase their interest and participation in learning. Based on the literature analysis, flashcards are not only effective for teaching the Indonesian language but also represent an innovative alternative to overcome educational challenges. In conclusion, this study confirms that flashcard media is a potential solution for Indonesian language instruction, positively impacting student motivation and learning outcomes in elementary schools.